Mechanisms of NMDA Receptor Inhibition by Biguanide Compounds - Arseniy S. Zhigulin; Anastasiya O. Novikova; Oleg I. Barygin (MDPI AG, 2024)
N-methyl-D-aspartate (NMDA) receptors are inhibited by many medicinal drugs. The recent successful repurposing of NMDA receptor antagonists ketamine and dextromethorphan for the treatment of major depressive disorder further enhanced the interest in this field. In this work, we performed a screening for the activity against native NMDA receptors of rat CA1 hippocampal pyramidal neurons among biguanide compounds using the whole-cell patch-clamp method. Antimalarial biguanides proguanil and cycloguanil, as well as hypoglycemic biguanide phenformin, inhibited them in micromolar concentrations, while another hypoglycemic biguanide metformin and antiviral biguanide moroxydine were practically ineffective. IC50 values at −80 mV holding voltage were 3.4 ± 0.6 µM for cycloguanil, 9.0 ± 2.2 µM for proguanil and 13 ± 1 µM for phenformin. The inhibition by all three compounds was not competitive. Cycloguanil acted as an NMDA receptor voltage-dependent trapping channel blocker, while proguanil and phenformin acted as allosteric inhibitors. Our results support the potential clinical repurposing of biguanide compounds for the treatment of neurodegenerative disorders linked to glutamatergic excitotoxicity while also providing a better understanding of structural determinants of NMDA receptor antagonism by biguanides.